1989
DOI: 10.1289/ehp.8981225
|View full text |Cite
|
Sign up to set email alerts
|

Environmental occurrence, abundance, and potential toxicity of polychlorinated biphenyl congeners: considerations for a congener-specific analysis.

Abstract: Polychlorinated biphenyls (PCBs) as environmental contaminants often cannot be adequately described by reference to Aroclors or to total PCBs. Although there are 209 possible PCB configurations (congeners), perhaps half that number account for nearly all of the environmental contamination attributable to PCBs. Still fewer congeners are both prevalent and either demonstrably or potentially toxic. If potential toxicity, environmental prevalence, and relative abundance in animal tissues are used as criteria, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
282
0
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 621 publications
(295 citation statements)
references
References 71 publications
7
282
0
6
Order By: Relevance
“…Exposure to PCBs in red-eared slider turtles is characterized by low concentrations of moderately chlorinated mono-ortho and di-ortho congeners (penta-, hexa-, and hepta-CBs). Congeners with 5-7 chlorine atoms are prevalent in the environment because they occur in greater proportions in many PCB formulations (McFarland and Clarke 1989). They are more often found in biota because they are not readily metabolized compared to less chlorinated PCBs, but also do not tightly bind to soil and sediment as do congeners with high chlorination (McFarland and Clarke 1989).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to PCBs in red-eared slider turtles is characterized by low concentrations of moderately chlorinated mono-ortho and di-ortho congeners (penta-, hexa-, and hepta-CBs). Congeners with 5-7 chlorine atoms are prevalent in the environment because they occur in greater proportions in many PCB formulations (McFarland and Clarke 1989). They are more often found in biota because they are not readily metabolized compared to less chlorinated PCBs, but also do not tightly bind to soil and sediment as do congeners with high chlorination (McFarland and Clarke 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Congeners with 5-7 chlorine atoms are prevalent in the environment because they occur in greater proportions in many PCB formulations (McFarland and Clarke 1989). They are more often found in biota because they are not readily metabolized compared to less chlorinated PCBs, but also do not tightly bind to soil and sediment as do congeners with high chlorination (McFarland and Clarke 1989). Polychlorinated biphenyl 153 (di-ortho) has been reported as the dominant PCB congener in many studies because it is not as easily biotransformed as other congeners (Safe 1984).…”
Section: Resultsmentioning
confidence: 99%
“…Polychlorinated biphenyls (PCBs) are environmental contaminants that have been found at high levels in human samples, like adipose tissue, breast milk, and ovarian follicle fluid [71][72][73]. Depending on their chemical structure, PCBs may act disruptive on estrogen, androgen, or thyroid hormone receptors and have been demonstrated to exert numerous adverse effects on reproduction, the immune system, and development [74][75][76][77].…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…Field studies have inferred POP biotransformation from lower measured biotransformation factors (i.e. lower relative concentrations in predator body residues compared to that in prey), lower concentrations relative to recalcitrant congeners such as PCB 153, or lower retention of congeners expected to be metabolized based on structure-activity relations [206][207][208][209][210][211]. However, these methods are indirect and do not provide conclusive evidence for in vivo biotransformation, underscoring the difficulty in unequivocally detecting biotransformation in aquatic food webs using achiral techniques alone, without the use of stable-carbon or radiolabeled tracers and the expenses involved therein.…”
Section: Oc Pesticides and Pcbsmentioning
confidence: 99%
“…Both PCBs 95 and 136 have vicinal meta/para hydrogen atoms, making them amenable to attack by CYP2B isozymes. It is not clear if CYP2B-like isozymes can be induced in fish [228,229], but if this degradation was catalyzed by CYP2B, then it is clear that conventional models of predicting CYP-mediated PCB degradation [206][207][208][209][210][211] do not properly account for enantiomer-specific degradation. Wiberg et al [230] suggested that the difference in degradation of these two congeners could be attributed to changes in chemical assimilation across the gastrointestinal tract from hydrophobicity and steric hindrance.…”
Section: Oc Pesticides and Pcbsmentioning
confidence: 99%